2015
DOI: 10.1002/etc.3179
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting PCB bioaccumulation patterns among Lake Huron lake trout reflect basin‐specific ecology

Abstract: This study collected multiple age classes of lake trout from Lake Huron's Main Basin, Georgian Bay, and North Channel regions to compare and contrast top predator polychlorinated biphenyl (PCB) bioaccumulation patterns in separate compartments of the same ecosystem. Sum PCB concentrations were highest for Main Basin (260 ± 24.9 ng g(-1) wet wt) fish, followed by Georgian Bay (74.6 ± 16.2 ng g(-1) ) and North Channel (42.0 ± 3.3 ng g(-1)) fish. Discriminant functions analysis of lake trout PCB profiles and stab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
30
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 43 publications
3
30
1
Order By: Relevance
“…For example, should prey communities, abundances, and food-web structures be similar across multiple compartments of the same ecosystem, this would be expected to manifest in similar magnitudes and patterns of congener bioaccumulation among individuals of the same species. That basin-specific PCB profiles have now been demonstrated for top predator (Paterson et al 2016) and secondary consumer forage fish species collected from across Lake Huron confirms conclusions regarding the importance of lower trophic level processes in regulating pollutant and energy transfer within the Lake Huron food webs (Bunnell et al 2014;Paterson et al 2014;McLeod et al 2019). Bunnell et al (2014) concluded that bottom-up control mechanisms predominate in terms of nutrient and energy availability and flow in Lake Huron.…”
Section: Discussionmentioning
confidence: 55%
See 4 more Smart Citations
“…For example, should prey communities, abundances, and food-web structures be similar across multiple compartments of the same ecosystem, this would be expected to manifest in similar magnitudes and patterns of congener bioaccumulation among individuals of the same species. That basin-specific PCB profiles have now been demonstrated for top predator (Paterson et al 2016) and secondary consumer forage fish species collected from across Lake Huron confirms conclusions regarding the importance of lower trophic level processes in regulating pollutant and energy transfer within the Lake Huron food webs (Bunnell et al 2014;Paterson et al 2014;McLeod et al 2019). Bunnell et al (2014) concluded that bottom-up control mechanisms predominate in terms of nutrient and energy availability and flow in Lake Huron.…”
Section: Discussionmentioning
confidence: 55%
“…Critically, these differences are likely due to ecological and biological mechanisms owing to an absence of spatial patterns in sediment PCB contamination and negligible historical differences in the extent of dissolved aqueous PCB concentrations within and among Lake Huron's basins (Glooschenko et al 1976;Anderson et al 1999;Gewurtz et al 2008). Paterson et al (2016) concluded that basin-specific PCB bioaccumulation profiles observed among Lake Huron lake trout were representative of high degrees of basin-fidelity, with differences in prey abundances, foraging ecologies, and growth patterns playing significant roles in the magnitude and patterns of PCB congener bioaccumulation in this top predator. For the forage fish included in the present study, contrasting congener bioaccumulation profiles among individuals of the same species but collected from different locations within Lake Huron suggest similar basin-specific processes regulating pollutant exposure and assimilation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations